Suggested learning tasks to develop visual discrimination skills to educable mentally retarded - Concepcion, Leni Leonor Saavedra 1932-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1975)
The main purpose of the study is to suggest basic learning tasks in reading through the development of visual discrimination skills of educable mentally retarded in the primary level. The learning tasks are categorized into the following four specific skills: 1) ability to identify objects in one's visual field, 2) ability to note likeness and differences, 3) ability to sort objects by categories, and 4) ability to differentiate figure-ground relationships.
Vita.
Thesis (Master of Arts in Teaching Special Education - Mental Retardation)--University of the Philippines, Diliman.
Keywords: Visual discrimination; Visual perception in children -- Philippines; Figure-ground perception -- Philippines; Children with mental disabilities -- Education -- Philippines; Special education -- Philippines